2011
DOI: 10.1016/j.toxlet.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Time-series analysis of gene expression profiles induced by nitrosamides and nitrosamines elucidates modes of action underlying their genotoxicity in human colon cells

Abstract: N-nitroso compounds (NOCs) may represent a carcinogenic risk to humans following endogenous colonic nitrosation processes. We used the colon adenocarcinoma cell line Caco-2 to investigate transcriptomic changes at three time points (1, 6, 24 h) following exposure to genotoxic concentrations of six different NOCs (two nitrosamides, four nitrosamines) with the purpose of identifying biological processes that may play a part in the carcinogenicity of these compounds. This is especially important for nitrosamide e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…For example, compounds identified as growth suppressive for the primary cells, eg, many of the fatty acids, nitrates, terpenoids, and curcuminoids, are all known to either promote differentiation or exhibit cell toxicity. 38 , 39 Glucoraphanin (#70), responsible for the bitterness of cabbage and Brussels sprouts, reduced epithelial cell numbers to near 0, consistent with its reported toxicity when consumed in large amounts. Enterolactone (#75, a microbial metabolite of flaxseed) increased cell numbers relative to that of the control, consistent with its failure to prevent intestinal adenoma formation and pose an increased cancer risk when at very high levels.…”
Section: Resultssupporting
confidence: 65%
“…For example, compounds identified as growth suppressive for the primary cells, eg, many of the fatty acids, nitrates, terpenoids, and curcuminoids, are all known to either promote differentiation or exhibit cell toxicity. 38 , 39 Glucoraphanin (#70), responsible for the bitterness of cabbage and Brussels sprouts, reduced epithelial cell numbers to near 0, consistent with its reported toxicity when consumed in large amounts. Enterolactone (#75, a microbial metabolite of flaxseed) increased cell numbers relative to that of the control, consistent with its failure to prevent intestinal adenoma formation and pose an increased cancer risk when at very high levels.…”
Section: Resultssupporting
confidence: 65%
“…To our knowledge this is the first to study the impact of carcinogens from smoking and red/processed meats on normal epithelial cells of the colon crypt stem cell niche, the expected target cell population for the origin of neoplastic changes [ 11 ]. Previous studies aimed to determine the transcriptomic response of smoking/red meat in the colon using patients already presenting with CRC [ 9 , 10 ], while studies of the individual chemical constituents of our carcinogen cocktail have been primarily performed in CRC cell lines [ 5 7 , 36 , 37 ]. These are unlikely to reflect the normal response of colon crypt epithelial cells to environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, our study does not model the infrequent dosing of carcinogens likely observed through smoking or dietary intake. The selection of dose for each compound was similar to doses chosen across numerous previous studies in different cell lines [ 5 , 7 , 36 , 37 , 54 57 ]. However, we note that the carcinogens doses chosen for this study are likely orders of magnitude greater than would be expected to be found in the colon from tobacco smoke inhalation and/or daily consumption of red/processed meats.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence reported a significant association between urinary NOC excretion and micronuclei frequency in human lymphocytes as well as gene expression changes associated with malignant cell transformation in NOC‐exposed Caco‐2 cells . Whole blood transcriptomes of 30 individuals were screened for transcription patterns correlating with NOC exposure markers and micronuclei frequency in lymphocytes .…”
Section: Potentially Detrimental Health Effects Of Nocmentioning
confidence: 99%